2011
DOI: 10.1007/s11010-011-0851-0
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2 (MMP-2) and -9 (MMP-9) in preoperative serum as independent prognostic markers in patients with colorectal cancer

Abstract: Colorectal cancer is one of the leading causes of cancer related death in developed countries. One of the reasons is the absence of tumor specific diagnostic and prognostic markers. The aim of this study was to examine the correlation of matrix metalloproteinase-2 (MMP-2) and -9 (MMP-9) expressions in serum and clinicopathological features of the colorectal adenocarcinoma. Another aim was to examine expression of MMP-9 in the tissue of the colorectal carcinoma in MMP-9 serum positive patients. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 29 publications
4
32
0
4
Order By: Relevance
“…Additionally, MMP-2 and MMP-9 were closely associated with lymph node metastasis, lymphatic invasion and prognosis of gastric cancer (32). Similar results have also been demonstrated in vitro, including gastric, ovarian and laryngeal cancer cells (33)(34)(35).…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, MMP-2 and MMP-9 were closely associated with lymph node metastasis, lymphatic invasion and prognosis of gastric cancer (32). Similar results have also been demonstrated in vitro, including gastric, ovarian and laryngeal cancer cells (33)(34)(35).…”
Section: Discussionsupporting
confidence: 76%
“…One study found that MMP-2 and -9 protein levels were expressed at significantly higher ratios in the sera of persons with CRC compared to normal controls. This finding had greater diagnostic sensitivity than two other biomarkers currently used in clinical practice, CEA and CA19-9 [16]. In T3-T4 node-negative CRC, MMP-9 over-expression, CEA greater than 5 ng/mL and lymphatic invasion were associated with poor prognosis.…”
Section: Specific Roles Of Mmps In Crcmentioning
confidence: 79%
“…Serum levels have thus been shown to correlate significantly with plasma levels in two different diseases (Gerlach et al , 2009). Serum MMP9 levels have also been shown to be significantly associated with breast cancer stage and size (Motovali-Bashi et al , 2010), gastric cancer stage (Dragutinovic et al , 2009), stromal reaction in gastric cancer (Shen et al , 2000), and CRC stage (Dragutinovic et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Serum MMP9 levels have recently been shown to be significantly elevated in CRC patients compared with controls, and higher in late-stage colorectal neoplasia as compared with early-stage disease (Dragutinovic et al , 2011). Our pilot work suggested that serum MMP9 estimation is an acceptable test and has a high sensitivity and negative predictive value for colorectal neoplasia (Hurst et al , 2007).…”
mentioning
confidence: 99%